Apocynin, an NADPH oxidase inhibitor, suppresses progression of prostate cancer via Rac1 dephosphorylation - Suzuki S. (2014)
Recently, considerable evidence has been generated that oxidative stress contributes to the etiology and pathogenesis of prostate cancer. The present study focused on the effects of apocynin, an inhibitor of the NADPH oxidase which generates intracellular superoxide, on a rat androgen-independent prostate cancer cell line (PLS10) in vitro and in vivo. Apocynin significantly inhibited cell proliferation of PLS10 cells via G1 arrest of the cell cycle in vitro. Surprisingly, it did not affect reactive oxygen species (ROS) but inhibited phosphorylation of Rac1, one component of the NADPH oxidase complex. A Rac1 inhibitor, NSC23766, also inhibited cell proliferation, and both apocynin and NSC23766 reduced phosphorylation of Rac1 and NF-κB, as well as cyclin D1. Furthermore, in a xenograft model of prostate cancer with PLS10, apocynin suppressed tumor growth and metastasis in a dose dependent manner in vivo, with reduction of cell proliferation and vessel number in the tumors. Expression and secretion of vascular endothelial growth factor (VEGF) were reduced by apocynin treatment in vivo and in vitro, respectively. In conclusion, despite no apparent direct relationship with oxidative stress, apocynin inhibited growth of androgen-independent prostate cancer in vitro and in vivo. Apocynin thus warrants further attention as a potential anti-tumor drug. © 2013 Elsevier GmbH.